Filsafat dan Sejarah Perkembangan Ilmu - Siti Mariyah; Ahmad Syukri; Badarussyamsi Badarussyamsi; Ahmad Fadhil Rizki (Undiksha, 2021)
Philosophy is a science that is extensive, meaning that it is closely related to our daily lives. In fact, it can be said that philosophy is the driving force of our daily lives as individuals and as collective human beings in the form of a society or nation. Bertrand Russell explained that “between theology and science lies in a no man's land. This area is under attack by both theology and science. This no man's land is called